Označevanje korpusov - Erjavec, Tomaž (Jezik in slovstvo, 2003)
Ordered collections of machine-readable texts, corpora, are useful in various branches of linguistics. The present paper focuses on the machine-readable form of corpora, above all on their annotation, i.e. adding interpretative information to the text in the corpus. The annotation presented is based on taking into consideration the international standards from this field, which contributes to better documentation and verifiability, easier use of processing applications, and better interchange and longevity. In the first part, corpus encoding standards, above all XML (eXtended Marup Language) and TEI (Text Encoding Initiative), are discussed, while in the second part some of the interesting levels of linguistic annotation of corpora are outlined.
Keywords: Slovene; slovenščina; Corpus linguistics; korpusno jezikoslovje; Language technology; jezikovne tehnologije